DIVERSIFIKASI POTENSI BERAS MERAH ORGANIK DESA SUMBEREJO MENJADI PEMBUATAN SEREAL - Utami, Intan Rahmatika El Putri; Sa’idah, Nely Meliatus; Afif, Rendi; Ulinnuha, Firda; Putri, Natasya Stivani; Putri, Sabrina Claudia Anggraini; Falah, Ahmad Naufal; Sukarno, Anggo Kusuma; Setiyono, Setiyono (Mafaza : Jurnal Pengabdian Masyarakat, 2025)
Sumberejo Village holds significant potential in the agricultural sector, particularly in the cultivation of organic red rice managed by a local farmer group. However, the utilization of the harvest has remained limited to sales in the form of unhusked or milled rice, without further product diversification. To enhance value-added potential and competitiveness, an innovation was introduced to process organic red rice into healthy cereal products. The Community Service Program (KKN) of the University of Jember collaborated with local partners, including a farmer group, the women’s organization (PKK), and the youth association (Karang Taruna) of Sumberejo Village, to conduct education and training activities focused on producing organic red rice-based cereal. The program involved a village potential survey, formulation of the work plan, and hands-on training in production techniques, marketing strategies, and product packaging. The results indicate an increase in the community’s knowledge and skills in diversifying agricultural products. This initiative has successfully created opportunities for entrepreneurship based on local resources and has contributed to strengthening the village’s food security through the sustainable development of economically valuable products.